Maintenance of sinus rhythm with an ablation strategy in patients with atrial fibrillation is associated with a lower risk of stroke and death. Issue 1 (19th September 2011) - Hunter, Ross J; McCready, James; Diab, Ihab; Page, Stephen P; Finlay, Malcolm; Richmond, Laura; French, Antony; Earley, Mark J; Sporton, Simon; Jones, Michael; Joseph, Jubin P; Bashir, Yaver; et al.
Abstract : Objective: To investigate whether catheter ablation of atrial fibrillation (AF) reduces stroke rate or mortality. Methods: An international multicentre registry was compiled from seven centres in the UK and Australia for consecutive patients undergoing catheter ablation of AF. Long-term outcomes were compared with (1) a cohort with AF treated medically in the Euro Heart Survey, and (2) a hypothetical cohort without AF, age and gender matched to the general population. Analysis of stroke and death was carried out after the first procedure (including peri-procedural events) regardless of success, on an intention-to-treat basis. Results: 1273 patients, aged 58±11 years, 56% paroxysmal AF, CHADS2 score 0.7±0.9, underwent 1.8±0.9 procedures. Major complications occurred in 5.4% of procedures, including stroke/TIA in 0.7%. Freedom from AF following the last procedure was 85% (76% off antiarrhythmic drugs) for paroxysmal AF, and 72% (60% off antiarrhythmic drugs) for persistent AF. During 3.1 (1.0–9.6) years from the first procedure, freedom from AF predicted stroke-free survival on multivariate analysis (HR=0.30, CI 0.16 to 0.55, p<0.001). Rates of stroke and death were significantly lower in this cohort (both 0.5% per patient-year) compared with those treated medically in the Euro Heart Survey (2.8% and 5.3%, respectively; p<0.0001). Rates of stroke and death were no different from those of the general population (0.4% and 1.0%, respectively). Conclusion: Restoration of sinus rhythm by catheter ablation of AF is associated with lower rates of stroke and death compared with patients treated medically.